An Exploratory Study to Assess the Factors Responsible for Stress among the Adolescents Studying at Select School of Rahata Tehsil, Ahmednagar District, M. S - Vinayak Dighe, Sharadchandra (Indian Journal of Nursing Sciences, 2024)
Introduction: Previous research studies show high prevalence of stress among the adolescents. It is significant to explore the factors responsible for stress among the adolescents so that preventive and remedial strategies may be planned. Therefore, the present study was conducted with the objectives (1) to assess the level of stress among adolescents, (2) to explore the factors causing stress among adolescents, and (3) to find out association of stress with their selected demographical variables. Materials and Methods: An exploratory study was conducted on 100 adolescents studying at select school of the Rahata Tehsil, M. S. Participants were recruited in the study by adapting purposive sampling technique. Data were collected using interview technique with the help of adolescent stress questionnaires which are a 56 items checklist with five point rating scale. Data were analyzed using descriptive and inferential statistics. Results: Findings of the study revealed factors responsible for stress among the adolescents which included home life, school performance, school attendance, peer pressure, interaction with the teachers, future uncertainty, conflicts in the school, financial pressure, and emerging adult responsibility. About 67% and 33% adolescents were having moderate and low stress, respectively. There was a significant association of stress with occupation of mother, religion, and family income. Conclusion: The present study reported moderate stress among 67% of the adolescents, which is alarming. This study highlights the need to orient parents and teachers to factors of stress and ways of modifying them.